Classroom learning environments: Retrospect, context and prospect - Fraser, Barry (Springer, 2012)
This chapter reviews four decades of research within the burgeoning field of classroom learning environments. One major thrust is a review of the development, validity and use of several frequently-used and extensively-validated learning environment questionnaires such as the Science Laboratory Environment Inventory, Constructivist Learning Environment Survey and the What Is Happening In this Class?, as well as some recent questionnaires such as the Technology-Rich Outcomes-Focused Learning Environment Inventory and Constructivist-Oriented Learning Environment Survey. Another purpose of this chapter is to review several lines of past learning environment research, including associations between student outcomes and the learning environment, evaluation of educational innovations, teachers’ action-research attempts to improve their classroom environments, links between educational environments, and cross-national studies.